Effectiveness of Instructional Program on Women Practices about Prevention of Covid 19 in Kirkuk City - Rabab Hamoudy Hanon, Rabea Mohsen Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pregnancy is a condition of partial immune suppression which makes pregnant women riskier to viral infections, and the morbidity is increased even with seasonal influenza. Therefore, the COVID-19 epidemic may have dangers consequences for pregnant women. Although the high incidence of cases of COVID-19 are currently in China, the risk of outward transmission appears to be significantly high global concern. Objectives: To assess pregnant women's practices about prevention of covid 19 before and after implementation of instruction program and to determine the effectiveness of instruction program on pregnant women practices about prevention methods of corona virus, covid 19 in PHCC in Kirkuk city. Methods: A quasi-experimental design was conducted during the period from (6th may 2021 through 20th August 2021) on non-probability sample (purposive) consists of (100) pregnant women) who visited the primary health care center. The sample practices was exposed to pretest, educational program, posttest. The study was conducted in Kirkuk city, Kirkuk health Director, three primary health care centers from the Kirkuk 1st sector which include (Al- Mansur center for primary health care, Al- Wassity center for primary health care, and Bader center for primary health care), than select three primary health care centers from Kirkuk 2nd sector which include (AL-Rasheed center for Primary health care, Azady center for Primary health care, AL-Nassir center for Primary health care, and Al- Mansur center for primary health care) Questionnaire was used as a tool of data collection. A pilot study was conducted at Al- Wassity center for primary health care in order to determine the reliability of the study and the testing the pregnant women practices about prevention methods of corona virus diseases 19. Data were collected through the questionnaire. Data were analyzed through the application of descriptive and inferential statistical data analysis approach through the use of (SPSS) version 22.0 and Excel system Results: The results of the study have revealed that significant correlation between pretest and posttest periods after the implementation of education program for pregnant women Practices regarding prevention methods of corona virus and reducing infected by it. There were high significant correlations between pre and post periods at (p. value: 0.101) in evaluation of the effectiveness of the instruction program in the practices of pregnant women on prevention methods to reduce the incidence of infection between Pre and post evaluation. Conclusions: The study concluded that the educational program can be considered as an effective mean for the improvement of the pregnant women's practices about the importance prevention methods of corona virus. Recommendations: Pregnant women should be given instructional booklets in order to raise practice level of preventive measures of COVID-19 infection at the beginning of their pregnancy and who can protect their families' members from such pandemic.